Artificial intelligence in justice - Karmaza, Oleksandra O.; Koroied, Sergii O.; Makhinchuk, Vitalii M.; Strilko, Valentyna Yu.; Iosypenko, Solomiia T. (Linguistics and Culture Review, 2021)
The relevance of this study is condition upon the necessity of an in-depth investigation of the phenomenon of artificial intelligence, including its use in the judicial system of various legal states and its impact on the entire judicial system of the state. In this regard, the present paper aims to cover the main definitions of the concept of artificial intelligence, its origins, characteristics, grounds for application, as well as direct interaction and influence on the implementation of the main tasks of justice through the use and development of artificial intelligence in the judicial procedure. The leading method of this study is dialectical, although the authors also employ a combination of other different methods of scientific cognition. The dialectical method, which underlies the theoretical work and is directly listed as fundamental, allowed thoroughly analysing the nature of the concept of artificial intelligence, its key advantages and disadvantages, by analysing its use in the legal systems of the world's leading states. This paper investigates the emergence and transformation of artificial intelligence in modern technological and information relations, its gradual introduction in various spheres of life, namely the ways of implementation and the possibility of application in justice.